2019
DOI: 10.1111/cid.12714
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐guided calvarial mono‐cortical bone blocks harvest: A novel approach for three‐dimensional alveolar reconstruction of atrophic maxilla

Abstract: Background Calvarial bone grafts have been one of the grafting options that provides predictable results for three‐dimensional reconstruction of severely atrophied ridges owing to their low resorption and rapid revascularization, thus providing adequate volume for implant insertion. The aim of this study was to introduce a computer‐guided technique for calvarial graft harvest to minimize the complications known with grafting from this donor site. Materials and Methods Eight patients, suffering from severely at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The studies were categorized according to the type of bone biomaterial into autologous, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] allogeneic [39][40][41] and xenogeneic 26,31,33,34,42 groups to facilitate the description of each type. It should be noted that a single study may investigate more than 1 type, which allows for a comprehensive description of each.…”
Section: Characteristics Of Patients and Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies were categorized according to the type of bone biomaterial into autologous, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] allogeneic [39][40][41] and xenogeneic 26,31,33,34,42 groups to facilitate the description of each type. It should be noted that a single study may investigate more than 1 type, which allows for a comprehensive description of each.…”
Section: Characteristics Of Patients and Study Proceduresmentioning
confidence: 99%
“…With regard to extraoral donor sites, bone can be harvest ed from the calvarium, anterior iliac crest, tibia, fibula, rib, and olecranon (proximal ulna). 26,28,[30][31][32][33]35 Intraoral donor sites encompass the mandible (chin/symphysis, ramus, retromolar area), zygoma and maxilla (tuberosity). [23][24][25]29,34,[36][37][38]43,44 With regard to one of the most common donor sites, the mandible, the utilization of the ramus as a donor site, as opposed to the symphysis, has been associated with several advantages.…”
Section: Autologous Bone Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Chappuis et al suggested that the greatest amount of bone loss is in the horizontal dimension and occurs mainly on the buccal aspect of the ridge. 3 Depending on the type of atrophy, different treatment modalities have been attempted for horizontal alveolar bone defect augmentation, including the use of particulate and block grafting materials, 4 distraction osteogenesis, guided bone regeneration (GBR), growth, and differentiation factors. 1 Recombinant human bone morphogenic protein (rhBMP) was also used for the reconstruction of horizontal bony defects: in 2009, Buser et al reported that GBR has become a predictable and well-documented surgical approach, it depends on the use of barrier membranes over a defect, promoting the ingrowth of osteogenic cells and preventing the migration of epithelial cells and fibroblasts from the overlying soft tissues into the wound.…”
Section: Introductionmentioning
confidence: 99%
“…Autogenous bone is the gold standard. [7][8][9] However, it costs an extra donor site morbidity and a longer surgical time for harvesting. The bones harvested from the iliac crest, the mandible, and the tibia were investigated by Holtgrave and Spiessl 10 , Mi Hyun Seo et al 11 , and Fethi Atil 12 , respectively.…”
Section: Introductionmentioning
confidence: 99%